De- and recellularization of the pig uterus: a bioengineering pilot study. Issue 1 (20th December 2016) - Campo, Hannes; Baptista, Pedro M; López-Pérez, Nuria; Faus, Amparo; Cervelló, Irene; Simón, Carlos
Abstract: Absolute uterine factor infertility, or the absence of a functional uterus, has a prevalence of 3%–5% in the general population. Despite the great strides being made in reproductive medicine, patients diagnosed with absolute uterine factor infertility remain untreatable. The only available solution has been gestational surrogacy, but recently the Brannström group presented a viable alternative by reporting the first successful live birth after uterus transplantation. Similar to other transplantations, this approach has inherent limitations such as the paucity of donor organs and the need for long-term immunosuppression. Whole organ de- and recellularization, a novel tissue engineering approach within the field of regenerative medicine, could eventually provide another solution. Several groups have described animal models in which they have performed decellularization of whole uteri, while maintaining the extracellular matrix to enable recellularization attempts. Our work offers a new perspective; in decellularizing the porcine uterus, this constitutes the first pilot study using large whole reproductive organs. We demonstrated the preservation of a reusable/functional extracellular matrix while maintaining its vascular network. Furthermore, we report the first use of human side population stem cells in the successful recellularization of small acellular disk scaffolds procured from the decellularized organs. To conclude, this research opens new avenues in whole uterus bioengineering, opening the way towards the transplantation of functional bioengineered uteri into humans. Summary Sentence: A novel decellularization protocol using SDS and Triton X-100 successfully converts large pig uteri into acellular bioscaffolds with potential for subsequent recellularization.